Signaling Mechanism of Poly(ADP-Ribose) Polymerase-1 (PARP-1) in Inflammatory Diseases - Ba, Xueqing (American Society for Investigative Pathology, 2011)
Poly(ADP-ribosyl)ation, attaching the ADP-ribose polymer chain to the receptor protein, is a unique posttranslational modification. Poly(ADP-ribose) polymerase-1 (PARP-1) is a well-characterized member of the PARP family. In this review, we provide a general update on molecular structure and structure-based activity of this enzyme. However, we mainly focus on the roles of PARP-1 in inflammatory diseases. Specifically, we discuss the signaling pathway context that PARP-1 is involved in to regulate the pathogenesis of inflammation. PARP-1 facilitates diverse inflammatory responses by promoting inflammation-relevant gene expression, such as cytokines, oxidation-reduction–related enzymes, and adhesion molecules. Excessive activation of PARP-1 induces mitochondria-associated cell death in injured tissues and constitutes another mechanism for exacerbating inflammation.